PRAKTIK DEMOKRASI MODERN DALAM PEMERINTAHAN NAGARI DI MINANGKABAU - Fitra Arsil; Mohammad Novrizal; Ryan Muthiara Wasti; Yunani Abiyoso; Ali Abdillah (Arena Hukum, 2022)
The adat governance of Minangkabau has adopted the democratic principles long before the 1945 Constitution of the Republic of Indonesia has such principles. This was due to the character of Minangkabau society and its culture which are inherited from their ancestors in Minangkabau society. This paper examines how forms of democratic practice in Minangkabau are related to democratic theory and the division of power. This normative legal research is supported by conducting interviews with some prominent adat figures in the Minangkabau society. In conclusion, it shows that the democratic principles in Nagari can exist until now because of the influence of adat figures. The adat figures preserve and combine such principles with religious norms as their indigenous values to be the main reference to run the Nagari.